2017
DOI: 10.1103/physrevb.95.014104
|View full text |Cite
|
Sign up to set email alerts
|

Flexocoupling impact on the kinetics of polarization reversal

Abstract: The impact of flexoelectric coupling on polarization reversal kinetics and space charge dynamics in thin films of ferroelectric-semiconductors has been theoretically studied.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…It was experimentally proved that, as shown in Fig. 11(c), the mechanical force shows a comparable ability relative with the electrically method for switching the domain of the Moreover, with the help of flexoelectricity, the self-polarization direction of ferroelectric thin films, which is of difficulty in control in previous studies, is feasible to be changed by tuning the substrate interfaces and film thicknesses [153,154]. Park et al [155] demonstrated that the multiple domain switching pathways in multiaxial ferroelectric materials can be selectively controlled by a newly realized trailing flexoelectric field, specifically, by the motion of a mechanically loaded scanning probe microscope tip.…”
Section: Domain Tailoring and Polarization Switchingmentioning
confidence: 93%
“…It was experimentally proved that, as shown in Fig. 11(c), the mechanical force shows a comparable ability relative with the electrically method for switching the domain of the Moreover, with the help of flexoelectricity, the self-polarization direction of ferroelectric thin films, which is of difficulty in control in previous studies, is feasible to be changed by tuning the substrate interfaces and film thicknesses [153,154]. Park et al [155] demonstrated that the multiple domain switching pathways in multiaxial ferroelectric materials can be selectively controlled by a newly realized trailing flexoelectric field, specifically, by the motion of a mechanically loaded scanning probe microscope tip.…”
Section: Domain Tailoring and Polarization Switchingmentioning
confidence: 93%
“…Mechanical writing of stable nanodomains in simple mono-domain ultrathin BaTiO 3 films or 100 nm-thick BiFeO 3 films, by applying a non-uniform loading force using the surface probe in PFM, has been reported by several groups [278][279][280][281]. The underlying mechanism of these observed mechanical switching phenomena is now widely accepted as a flexoelectric effect, which is caused by the strong coupling between polarization and strain gradient induced by the probe-induced non-uniform force [278,282,283]. Similar switching phenomena of writing stable nanodomains in BaTiO 3 or BiFeO 3 films have so far not been observed in in situ TEM.…”
Section: Mechanical Switchingmentioning
confidence: 98%